1998
DOI: 10.1046/j.1570-7458.1998.00385.x
|View full text |Cite
|
Sign up to set email alerts
|

The relative performance of pheromone and light traps in monitoring the seasonal activity of both sexes of the eastern hemlock looper, Lambdina fiscellaria fiscellaria

Abstract: The seasonal flight activity of both sexes of the eastern hemlock looper, Lambdina fiscellaria fiscellaria Guenée (Lepidoptera: Geometridae) was studied during two consecutive years in Quebec and Newfoundland, using light (L), pheromone (P) and combined light and pheromone (LP) traps. Moth density significantly affected the performance of the different traps, with P traps being more effective at low than high density. However, P trap catches decreased just prior to the onset of female captures, probably as a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
47
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 33 publications
(55 reference statements)
8
47
0
Order By: Relevance
“…Differences in catches from pheromone and light traps have not so far been satisfactorily explained by any author. Temporal differences in the efficacy of light and pheromone traps have also been reported previously (Srivastava and Srivastava 1989;Campbell et al 1992;Delisle et al 1998). It has been suggested that this occurs because at high moth populations, pheromone traps are 'out-competed' by calling females.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Differences in catches from pheromone and light traps have not so far been satisfactorily explained by any author. Temporal differences in the efficacy of light and pheromone traps have also been reported previously (Srivastava and Srivastava 1989;Campbell et al 1992;Delisle et al 1998). It has been suggested that this occurs because at high moth populations, pheromone traps are 'out-competed' by calling females.…”
Section: Discussionsupporting
confidence: 69%
“…Pheromone traps can be used to monitor the temporal fluctuations, spatial distributions and abundances of insects of economic importance. Furthermore, because pheromone traps are species-specific, assessment of the abundance of the particular insect is less labour-intensive, which can make them a more cost-effective technique than light traps (Delisle et al 1998). In addition, pheromone traps can attract the target insect from considerable distances away (Ostrand and Anderbrant 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is a polyphagous herbivore, with larvae feeding on a variety of coniferous and deciduous trees (Carroll, 1956;Hébert et al, 2006;Berthiaume, 2007). Moths emerge from mid-August to late September and thus females lay eggs in late summer -early fall (Carroll, 1956;Delisle et al, 1998). Eggs are laid singly or in small groups of two or three on tree trunks or branches (Carroll, 1956) and they enter diapause for about 3 months (Delisle et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In these species, females rapidly lose weight after emergence as a result of egg-laying (Boggs 1997), and measurement of dry weight of field-collected specimens can be used to simulate the number and proportion of eggs laid by females relative to their potential fecundity (Lyons 1996). Equations describing the triangulation between potential fecundity (estimated using an indicator of body size), dry weight and realized fecundity (proportion of eggs laid by females at the time of sampling) are derived by rearing field-collected pupae to adulthood in the laboratory and allowing them to lay known numbers of eggs over different time intervals (Delisle et al 1998;Rosenheim et al 2008;Thomas 1978). The approach is depicted in Fig.…”
Section: Introductionmentioning
confidence: 99%